On-Line Energy-Use Benchmarking System for Industries in Malaysia - Ernest, Kamala (2004)
The study is intended to explore the viability of developing a web-based tool to facilitate a holistic approach to energy-use benchmarking management in the Malaysian Industrial sector. Energy-use benchmarking uses the measure of the plant’s specific energy consumption to assess its energy performance, which latter can be used as a baseline for future energy efficiency and energy conservation activities. The measures can also be used to chart out future energy policies related to the development of national energy sector. The system developed is a migration of the manual data collection system which has limitations to the number of companies that can use the same. The energy-use benchmarking community which is customarily known as the Industrial Energy Efficiency Community (IEEC) was created as part of the National Productivity Corporation’s (NPC) Benchmarking On-line Networking Database (BOND). Currently, the community has a membership of industries from eight energy intensive sectors in Malaysia, and this will be extended to the entire industrial sectors in stages. Among others, the on-line tool developed can perform automatic statistical analysis in computing energy-use benchmarks, evaluating performance of the community, and ranking companies’ performance according to selected indicators. In order to evaluate the usability of the system, a sample of four companies from the wood sector were selected. A survey conducted among the selected factories on the usability of the system showed 83 % favorable. However, there are still opportunities available for enhancement of the tool for better usability that can result in more competitive benchmarking analysis. Further descriptive statistics can be derived from the collected and analyzed data. Analysis shows that there is a performance gap of 59 % among the selected sample companies, which can work together to close this gap through end-use energy efficiency. Through daily monitoring and setting targets for determining slack in energy performance and improving end-use energy efficiency respectively, the participating industries can arrest not only fast depletion of fossil fuel reserves but also the negative impact to the environment due to the excessive emission of greenhouse gasses (GHG).